Fake news and the political economy of the media: A perspective of Ghanaian journalists - Paul Achonga Kabah Kwode; Nkosinathi Selekane (Communicare)
The enduring rate at which fake news is disrupting the political economy of the media is the subject of this study. Using a largely qualitative instrument of intensive interviews with 18 journalists purposively selected for the study, we discovered that fake news is one of the banes of journalism in Ghana. Fake news's notorious role in the political and economic realities of the country is not uncommon, as it has created uncountable political controversies. With several of the country's media owned by politicians or persons with a vested interest in politics, it became a practice for players to utilise fake news as a propaganda tool to outwit their competitors through the media. For these architects to fully achieve their goal, social media and affiliated mainstream media were used as instruments to propagate fabricated content against their opponents, especially during the 2020 general elections. This paper also identified the use of artificial intelligence and robotics in the creation of fake news content. The study recommends the need for media organisations in the country to seek the services of fact-checkers as a means of verifying stories, as well as to intensify education on the identification of fake news and possible flagging.